S100B increases in cyanotic versus noncyanotic infants undergoing heart surgery and cardiopulmonary bypass (CPB). (3rd April 2019) - Varrica, Alessandro; Satriano, Angela; Gavilanes, Antonio D. W.; Zimmermann, Luc J.; Vles, Hans J. S.; Pluchinotta, Francesca; Anastasia, Luigi; Giamberti, Alessandro; Baryshnikova, Ekaterina; Gazzolo, Diego
Abstract: Aims: S100B has been proposed as a consolidated marker of brain damage in infants with congenital heart disease (CHD) undergoing cardiac surgery and cardiopulmonary bypass (CPB). The present study aimed to investigate whether S100B blood levels in the perioperative period differed in infants complicated or not by cyanotic CHD (CHDc) and correlated with oxygenation status (PaO2 ). Methods: We conducted a case-control study of 48 CHD infants without pre-existing neurological disorders undergoing surgical repair and CPB. 24 infants were CHDc and 24 were CHD controls. Blood samples for S100B assessment were collected at six monitoring time-points: before the surgical procedure ( T 0), after sternotomy but before CPB ( T 1), at the end of the cross-clamp CPB phase ( T 2), at the end of CPB ( T 3), at the end of the surgical procedure ( T 4), at 24 h postsurgery ( T 5). Results: In the CHDc group, S100B multiples of median (MoM) were significantly higher ( p  < .05, for all) from T 0 to T 5. PaO2 was significantly lower ( p  < .05, for all) in CHDc infants at T 0– T 1 and at T 4 while no differences ( p  > .05, for all) were found at T 2, T 3, T 5. Linear regression analysis showed a positive correlation between S100B MoM at T 3 and PaO2 ( R  = 0.84; p  < .001). Conclusions: The present data showing higher hypoxia/hyperoxia-mediated S100B concentrations in CHDc infants suggest that CHDc are more prone to perioperative brain stress/damage and suggest the usefulness of further investigations to detect the "optimal" PaO2 target in order to avoid the side effects associated with reoxygenation during CPB.